Cultural Divergence in Emotion Regulation: U.S. and Korean Relationship Dynamics During Social Crises - Min Young Kim (Social Sciences, 2025)
(1) Background: In times of social crisis, the way individuals manage their emotions undergoes substantial changes. As emotion regulation strategies also vary across cultures, how they impact relationship dynamics between U.S. and Korean populations may differ. This study explores these cultural differences, shedding light on the interplay between culture, emotion, and social dynamics. (2) Methods: Through analysis of 210 U.S. and 197 Korean participants, the research investigated three relationship categories: spousal/couple relationships, family relationships, and friendships during social crisis. (3) Results: Using moderated mediation analysis, results revealed distinct patterns in ER’s mediating effects across these relationship types, with notable cultural variations. In spousal relationships, ER partially mediated the NA-relationship quality association among American participants but showed no mediation effect among Korean participants. Family relationships demonstrated complete ER mediation across both cultural groups, while friendships showed partial mediation effects regardless of cultural background; (4) Conclusions: These findings highlight how relationship type and cultural context jointly shape the role of emotion regulation in relationship quality, advancing our understanding of emotional dynamics across different cultural and relational settings. The study provides implications for developing culturally sensitive approaches to relationship maintenance and intervention strategies.